Maintaining resilience in the ASALs of Kenya: A perspective on stocking rates in extensive livestock systems - Msangi, Siwa; Signorelli, Sara (International Livestock Research Institute, 2016)
In this analysis, we make use of household level data to illustrate some very basic characteristics of pastoral livestock keepers, so that we can represent their behavior and adjustment to environmental shocks. This approach enables us to highlight some critical dimensions of vulnerability, and point to potential avenues for strengthening their resilience. Overall, the dryland regions of Kenya face high and widespread vulnerability to hunger, caused by a number of proximate factors; including weakness of infrastructure, governance, and exposure to climatic variability. A significant portion of arable land is arid or semi-arid, and crop-based agriculture is difficult to maintain in those areas. The heavy dependence of the extensive livestock systems in that region on the highly-variable availability of forage and herbaceous biomass is one of the key sources of vulnerability faced by livestock keepers.